2003
DOI: 10.1076/jcen.25.7.979.16481
|View full text |Cite
|
Sign up to set email alerts
|

A Validation of the Test of Memory Malingering in a Forensic Psychiatric Setting

Abstract: The Test of Memory Malingering (TOMM) has not been adequately validated in a forensic psychiatric setting. Dissimulation of cognitive impairment, as assessed by the TOMM, was evaluated in a group of 25 forensic inpatients admitted for evaluation of Competency to Stand Trial (CST/MSO group), and hypothesized to be at higher risk for feigning cognitive impairment. A comparison group of 36 patients, who were either civilly committed or adjudicated Not Guilty by Reason of Insanity (CIVIL/NGRI group), were hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 64 publications
(32 citation statements)
references
References 36 publications
0
32
0
Order By: Relevance
“…These findings might reflect either the greater sensitivity of the TOMM to detecting subtle forms of malingering, or might indicate a tendency to over-classify malingering. Given that other research has not supported the latter conclusion (Rees et al, 1998;Weinborn et al, 2003), the former appears more likely, although further research using analog methods is necessary to fully understand these associations.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…These findings might reflect either the greater sensitivity of the TOMM to detecting subtle forms of malingering, or might indicate a tendency to over-classify malingering. Given that other research has not supported the latter conclusion (Rees et al, 1998;Weinborn et al, 2003), the former appears more likely, although further research using analog methods is necessary to fully understand these associations.…”
Section: Discussionmentioning
confidence: 93%
“…Scores below 45 (90% correct) on the second or retention trial suggest that respondents have not performed to the best of their abilities (Tombaugh, 1996). Normative data indicate that, unlike the FIT, the TOMM is highly accurate in differentiating malingering individuals from normal controls (Rees et al, 1998;Weinborn, Orr, Woods, Conover, & Feix, 2003). Although persons with dementia appear apt to fail the TOMM, most genuinely impaired patients perform well above cutoffs on this measure (Teichner & Wagner, 2004;Tombaugh, 1997).…”
Section: Test Of Memory Malingering (Tomm)mentioning
confidence: 97%
“…Two studies (Batt, Shores, & Chekaluk, 2008;Loring et al, 2011) using differing methodological approaches to temporarily Batt et al (2008) found greater reduction in performance on the WMT versus the TOMM in a traumatic brain injury (TBI) sample under a cognitive distraction task condition. From a clinical groups perspective, while it is welldocumented that some individuals with significant cognitive impairment (e.g., bilateral hippocampal atrophy; GoodrichHunsaker & Hopkins, 2009) can perform well on published PVTs, there is also a growing body of literature indicating that some moderate to severely impaired clinical groups with no incentive to malinger or supply poor effort produce unacceptably low specificity rates, and this appears to vary across individual PVTs (Gorissen, Sanz, & Schmand, 2005;Greve et al, 2008;Howe & Loring, 2009;Merten, Bossink, & Schmand, 2007;Rudman, Oyebode, Jones, & Bentham, 2011;Weinborn, Orr, Woods, Conover, & Feix, 2003;but cf. Chafetz, Prentkowski, & Rao, 2011;Schroeder & Marshall, 2010).…”
Section: Classification Accuracy Of the Forced-choice Recognition Memmentioning
confidence: 99%
“…Specifically, components that were deemed to be less likely to contribute to the overall PVT performance were (2011) 79 Batt et al (2008) 75.5 c Barhon et al (in press) 96 Bolan et al (2002) 100 Gervais et al (2004) 89 Green (2011) 93.5 Greve, Bianchini, & Doane (2006) 96 Greve, Bianchi, Black, et al (2006) 82 Merten et al (2007) 91.5 c Tan et al (2002) 80 Teichner & Wagner (2004) 24/91.7 Tombaugh (1996) 86.5 c Tombaugh (1997) 91.28 c Weinborn et al (2003) 83.3 Weinborn et al (2012) 100 c 876 A. Leighton et al…”
Section: Cognition and Performance Validity Testsmentioning
confidence: 99%
“…A study by Gierok, Dickson, and Cole (2005) found that patients with pending legal charges exerted less effort on the TOMM than those with no obvious secondary gain while Weinborn, Orr, Woods, Conover, and Feix (2003) found that adjudicated forensic patients did significantly better than did patients still facing legal charges. Thus, a decision was made to include only patients who were no longer facing legal charges in an attempt to eliminate any external incentive to malinger.…”
mentioning
confidence: 99%